A world-wide study on delirium assessments and presence of protocols - Nydahl, Peter; Liu, Keibun; Bellelli, Giuseppe; Benbenishty, Julie; van den Boogaard, Mark; Caplan, Gideon; Chung, Chi Ryang; Elhadi, Muhammed; Gurjar, Mohan; Heras-La Calle, Gabi; Hoffmann, Magdalena; Jeitziner, Marie-Madlen; et al. (Age & ageing, 2024)
Delirium is a common complication of older people in hospitals, rehabilitation and long-term facilities.To assess the worldwide use of validated delirium assessment tools and the presence of delirium management protocols.Secondary analysis of a worldwide one-day point prevalence study on World Delirium Awareness Day, 15 March 2023.Cross-sectional online survey including hospitals, rehabilitation and long-term facilities.Participating clinicians reported data on delirium, the presence of protocols, delirium assessments, delirium-awareness interventions, non-pharmacological and pharmacological interventions, and ward/unit-specific barriers.Data from 44 countries, 1664 wards/units and 36 048 patients were analysed. Validated delirium assessments were used in 66.7% (n = 1110) of wards/units, 18.6% (n = 310) used personal judgement or no assessment, and 10% (n = 166) used other assessment methods. A delirium management protocol was reported in 66.8% (n = 1094) of wards/units. The presence of protocols for delirium management varied across continents, ranging from 21.6% (on 21/97 wards/units) in Africa to 90.4% (235/260) in Australia, similar to the use of validated delirium assessments with 29.6% (29/98) in Africa to 93.5% (116/124) in North America. Wards/units with a delirium management protocol [n = 1094/1664, 66.8%] were more likely to use a validated delirium test than those without a protocol [odds ratio 6.97 (95% confidence interval 5.289-9.185)]. The presence of a delirium protocol increased the chances for valid delirium assessment and, likely, evidence-based interventions.Wards/units that reported the presence of delirium management protocols had a higher probability of using validated delirium assessments tools to assess for delirium.